(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This scientific article analyzes the membership of rights holders in the organization, which is one of the important elements characterizing the organization of collective management. Also, a large number of cases of unlawful use of copyright works and unfair payment of copyrights to authors, the growing need to develop the institution of management of the author’s property rights on a collective basis determine the prospects for revising existing agreements. The article focuses on some current issues related to the improvement of this institute, as well as the opinions of scientists from Uzbekistan and other countries.Proposals and recommendations of scientific and practical importance for the development of copyright were put forward.